Silver, biofilms and wounds: resistance revisited. (4th March 2019) - Percival, Steven L.; Salisbury, Anne-Marie; Chen, Rui
Abstract: Silver is added to an array of commercially available healthcare products including wound dressings. However, overuse of silver is being raised as a potential health concern due to the possible selection of tolerant or resistant bacteria and as a factor that may induce cross resistance to antibiotics. To date, there are only a limited number of studies that have documented evidence of silver resistance in bacteria isolated from medical situations. These studies have indicated low levels of silver resistance in bacteria. However, in comparison to antibiotics, only a small number of studies have been undertaken to investigate silver resistance. It is clear that more studies are required to confirm the most effective therapeutic levels of silver that are needed to kill microbes. In addition, it is probable that sub-therapeutic levels of silver may potentially select for enhanced microbial tolerance. Nevertheless, to date, there still remains very little evidence that silver resistance is a growing health concern in wound care; more studies are clearly needed to substantiate this concern, which has not been observed clinically to any major degree. The issue of biofilm tolerance to silver is more complicated and data on the effect of silver on biofilms is sparse at present.